Determining the directional strain shift coefficients for tensile Ge: a combined x-ray diffraction and Raman spectroscopy study. (11th January 2017) - Etzelstorfer, Tanja; Wyss, Andreas; Süess, Martin J; Schlich, Franziska F; Geiger, Richard; Frigerio, Jacopo; Stangl, Julian
Abstract: In this work the calibration of the directional Raman strain shift coefficient for tensile strained Ge microstructures is reported. The strain shift coefficient is retrieved from micro-Raman spectroscopy measurements in combination with absolute strain measurements from x-ray diffraction using focused synchrotron radiation. The results are used to fit the phonon deformation potentials. A linear dependence of the phonon deformation potentials p and q is revealed. The method can be extended to provide strain calibration of Raman experiments also in other material system.